Ready to restore : the layman's guide to Christian counseling - Adams, Jay E. (Phillipsburg, New Jersey : Presbyterian and Reformed Publishing Co., 1981)
Here, at last, is a guide to Christian counseling written specifically for laymen. Dr. Adams wrote this book in response to hundreds of requests from Christian laymen and pastors. It provides help in a form that is both simple and nontechnical, yet biblical and comprehensive. Although Ready to Restore is simple and easy to use as a beginning textbook, unlike many simple books it is neither simplistic nor superficial. Its contents are the fruit of the author's arduous Bible study as well as his long and successful ministry of the Word in counseling. The chapters comprise a true picture of Christian counseling in a coherent and systematic way. This book can be used effectively for individual study, but the content, scope, format, and language have been especially designed for textbook use in Bible colleges, churches, Bible study groups, prayer meetings, or older youth groups. - Back cover.
Who should counsel? -- Goals, attitudes and dangers -- What is counseling? -- Ready to restore -- What about unbelievers? -- The counseling process -- Twenty-five basic principles -- Discipline : a two-edged sword -- Help on data gathering -- A biblical analysis of the problem -- Finding the biblical solution -- Implementing a biblical plan -- Follow through : working the plan -- Using homework -- Problems frequently faced -- How to grow as a counselor -- Conclusion -- Appendices. The personal data inventory -- The counselor's topical worklist.
Includes bibliographcal references.
Keywords: Pastoral counseling